If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -1z) = 7h (2x * 5 + -1z * 5) = 7h (10x + -5z) = 7h Solving 10x + -5z = 7h Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5z' to each side of the equation. 10x + -5z + 5z = 7h + 5z Combine like terms: -5z + 5z = 0 10x + 0 = 7h + 5z 10x = 7h + 5z Divide each side by '10'. x = 0.7h + 0.5z Simplifying x = 0.7h + 0.5z
| x^3+2x^2-8x-16=0 | | 5(x-5)=x(14-4) | | 5(2x-4)=2(3x+2) | | -7(p+7)=-21 | | 38+x=2(11+x) | | 4(3x-5)=2(x-5) | | 6(m+3)=2(m-1) | | -1-x^2=0 | | 56=-8(1+n) | | 0=4+2x-2x | | 2(4x+3)=3(2x+4) | | -(v+6)=-14 | | x^2+36x=0 | | 3(2x-3)=5(x+1) | | 8(x+9)=8x+72 | | 3x-2y-4=7y+6 | | 3x-5=x^2 | | (x+4)(2x+1)=(2x+5)(2-x) | | 27x+9=3x+30+3x | | A=1/2*70(40+160) | | 13m+3n-6m+9n= | | -4x^2-12x-3=0 | | (x+0.6)(x+1.6)=0 | | y=-16x^2 | | (2x-3)*(x+5)+7=(x-4)*(2x-1)+20 | | 7x^3+y^3+3xy(x-y)-12x^2+6x=1 | | 4x-(x+3)=(2x+5) | | (2x-3)*(x+5)+7=(x-4)*(2x-1)+2 | | x/2+x/3+200=x | | 4x^2=13x-3 | | -1*25= | | 3x+2y=4z |